Farewell to JEPS!. Issue 2 (12th January 2016) - Morton, Rebecca B.; Tucker, Joshua A.
Abstract : It is hard to believe that we have been at this for four years, but our term as editors is coming to a close. During this time, JEPS has gone from being little more than an idea in a few people's minds to a full fledged journal with robust submissions, excellent reviewers, and valuable published research from a wide range of scholars featuring all different types of experimental analyses employed in the study of politics. We are extremely excited by what JEPS has become, and we hope you share our enthusiasm!